2020
DOI: 10.3389/fpls.2020.548032
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis GEX1 Is a Nuclear Membrane Protein of Gametes Required for Nuclear Fusion During Reproduction

Abstract: During the life cycle of flowering plants, nuclear fusion, or karyogamy, occurs three times: once during female gametogenesis, when the two polar nuclei fuse in the central cell, and twice during double fertilization. In Arabidopsis thaliana , nuclear fusion events during sexual reproduction proceed without the breakdown of the nuclear envelope, indicating that nuclear membrane fusion is essential for the completion of this process. Arabidopsis gamete expressed 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…The GO term ‘karyogamy’ came up in cluster 3, mainly consisting of genes highly expressed in both egg and antheridia (Table S12). This includes GAMETE EXPRESSED1 ( GEX1 ), encoding a membrane protein homologous to the yeast karyogamy protein Kar5 (Beh et al ., 1997; Alandete‐Saez et al ., 2011; Ning et al ., 2013; Speijer et al ., 2015; Nishikawa et al ., 2020). GEX1 is localized to the nuclear membrane of the egg and central cell, and, upon double fertilization, it is required for sperm nuclear fusion in both cells.…”
Section: Resultsmentioning
confidence: 99%
“…The GO term ‘karyogamy’ came up in cluster 3, mainly consisting of genes highly expressed in both egg and antheridia (Table S12). This includes GAMETE EXPRESSED1 ( GEX1 ), encoding a membrane protein homologous to the yeast karyogamy protein Kar5 (Beh et al ., 1997; Alandete‐Saez et al ., 2011; Ning et al ., 2013; Speijer et al ., 2015; Nishikawa et al ., 2020). GEX1 is localized to the nuclear membrane of the egg and central cell, and, upon double fertilization, it is required for sperm nuclear fusion in both cells.…”
Section: Resultsmentioning
confidence: 99%
“…Localization and knock-out studies will be necessary to further elucidate their role during gametangia recognition and gamete fusion. Successful gamete fusion in most eukaryotic lineages is mediated by the plasma membrane-associated Hap2 fusogen protein (Wong and Johnson 2010) while the Gex1/Kar5/Brambleberry nuclear membrane protein is involved in nuclear fusion (karyogamy) (Nishikawa et al 2020). Strikingly, homologs for both genes are missing from the gene repertoire of sexual diatoms P. multistriata and S. marinoi (Ferrante et al 2019), suggesting the presence of alternative fusogens or of highly diverged Gex1 and Hap2 genes.…”
Section: Skeletonema Marinoi Sig10mentioning
confidence: 99%
“…We also showed that Arabidopsis gamete-expressed 1 (AtGEX1) is a nuclear membrane protein necessary for nuclear fusion during Arabidopsis reproduction [ 8 ]. The AtGEX1 gene was identified by screening genes that are expressed in the sperm cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…AtGEX1 is also involved in sperm nuclear fusion in the fertilized egg and central cells. The resulting gex1-1 homozygous mutant seeds showed aberrant endosperm proliferation and defects in early embryo development, which resulted in seed abortion [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation